Way of Intelligence - "Krishnamurti,J." (Chennai, 2012)
The way of Intelligence consists of a series of dialogues on ancient Indian Religious and philosophical themes. The ideas of causality, of a guru as a spiritual guide, of the spiritual path and of the goal, of the search for liberation, and of Sadhana or the right means thereto are all dealt with in a contemporary idiom. Throughout, Krishnamurti's concern is to lay bare the experiential component behind these terms and to lead his audience to the heart of the human problem. These penetrating dialogues reveal Krishnamutri at the height of his power
Keywords: The future of man